2018
DOI: 10.1111/ggr.12213
|View full text |Cite
|
Sign up to set email alerts
|

Rutile R632 – A New Natural Reference Material for U‐Pb and Zr Determination

Abstract: A new natural rutile reference material is presented, suitable for U‐Pb dating and Zr‐in‐rutile thermometry by microbeam methods. U‐Pb dating of rutile R632 using laser ablation ICP‐MS with both magnetic sector field and quadrupole instruments as well as isotope dilution‐thermal ionisation mass spectrometry yielded a concordia age of 496 ± 2 Ma. The high U content (> 300 μg g−1) enabled measurement of high‐precision U‐Pb ages despite its young age. The sample was found to have a Zr content of 4294 ± 196 μg g−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 34 publications
(84 reference statements)
1
28
0
Order By: Relevance
“…(). A new natural rutile reference material R632 was presented, suitable for U‐Pb dating by microanalytical methods (Axelsson et al ).…”
Section: Scientific Journals From Which Relevant Articles Were Reviewedmentioning
confidence: 99%
“…(). A new natural rutile reference material R632 was presented, suitable for U‐Pb dating by microanalytical methods (Axelsson et al ).…”
Section: Scientific Journals From Which Relevant Articles Were Reviewedmentioning
confidence: 99%
“…Note the wide range in color exhibited by the grains, the uneven fracture and the high surface reflectivity (adamantine luster), which is typical of rutile, a consequence of the high refractive index of the mineral. (c) Reflected light optical microscopy image of polished R632 [41] rutile grains. (d) Rutile grains separated from Sugluk-4 granulite facies quartzite.…”
Section: Rutile Reference Materials For La Icp-ms U-pb Datingmentioning
confidence: 99%
“…138,139 The incorporation of Zr into rutile during formation is strongly temperature-dependent, so rutile can be potentially used for both geochronology and/or Zr-in-Rutile (ZiR) thermometry. 166 However, the typically low U content in rutile may limit its applicability to LASS, particularly for small grains.…”
Section: Minerals Utilized For U-th-pb Dating and Lassmentioning
confidence: 99%
“…For apatite, several LA-ICP-MS geochronology reference materials with a range of ages are widely available including Durango, 167 McClure Mountain, 168 Kovdor, Otter Lake and Slyudyanka, 45 MAD, 56 Among these materials, NW-1 apatite, extracted from a carbonatite collected from the Prairie Lake alkaline-carbonatite complex in Ontario, Canada, is probably the best characterized over a range of isotopic systems, and has the lowest common lead content (0.75 ppm, with a 204 Pb-based f 206 of 0. 166 reported that R632 has a relatively low common Pb content (<1%; f 206 % < 1%), a relatively high U content (>300 ppm) and a moderate U-Pb age of 496 AE 3 Ma. Furthermore, the homogeneous and high Zr content of R632 (4294 AE 196 ppm) makes it a suitable reference material for Zr-in-rutile thermometry.…”
Section: Minerals Utilized For U-th-pb Dating and Lassmentioning
confidence: 99%